Warm-Ups and Coaches' Perceptions: Searching for Clues to Improve Injury Prevention in Youth Basketball - Anu M. Räisänen; Oluwatoyosi B. A. Owoeye; Oluwatoyosi B. A. Owoeye; Kimberley Befus; Carla van den Berg; Kati Pasanen; Kati Pasanen; Kati Pasanen; Kati Pasanen; Carolyn A. Emery; Carolyn A. Emery; Carolyn A. Emery; et al. (Frontiers Media S.A., 2021)
Introduction: Regular use of neuromuscular training (NMT) warm-up programs improves performance and prevents injuries. However, low level of adoption of these programs remains a problem. Understanding the current warm-ups in youth basketball and coaches' perceptions on injury prevention can guide the design of superior implementation strategies. This study describes warm-ups in youth basketball and coaches' injury prevention-related knowledge, attitudes, beliefs, and information sources.Methods: Youth basketball coaches (n = 50) completed a preseason questionnaire. The questionnaire covered warm-up length, use of aerobic/agility/balance/strength/other exercises in the warm-up, injury-related knowledge, attitudes, beliefs, and sources of information.Results: Typical warm-up duration was ≤ 10 min (48.0% of coaches, 95% CI: ±13.8%). All coaches included aerobic exercises in their warm-up. Agility, strength, and balance exercises were utilized by 80.0% (95% CI: ±11.7%), 70.7% (95% CI: ±13.6%), and 26.8% (95% CI: ±13.6%) of coaches, respectively. Most coaches agreed to some extent that basketball injuries are preventable (94%) and that participating in a NMT warm-up program would reduce player's risk of injury (92%). Other coaches were identified as the most common source of information on warm-ups and injury prevention.Discussion: Coaches use parts of effective NMT warm-up programs, but balance exercises are not well adopted. Considering the level of evidence supporting the importance of balance exercises in injury prevention, it is crucial to improve the implementation of NMT warm-up programs in youth basketball, for example, through educational courses. As fellow coaches were identified as the most important source of information, coaches' role in knowledge translation should be emphasized.